Cultural Politics, Ideology, and Methodology in Disproportionality Research: A Rejoinder. (September 2019) - Anastasiou, Dimitris; Kauffman, James M.
We summarize the role of cultural politics in special education. We analyze the 2019 discourse of Whitford and Carrero, our respondents, about the role of ideology and models of disability. Our comments further explain how we see the relationship between theorizing and reality. We contrast the deficit thinking rhetoric with the Individuals With Disabilities Education Act's legal model in the disability identification. We review the recent evidence in the disproportionality research and discuss methodological issues raised by our respondents. Our focus is the phantom menace variable that characterizes part of disproportionality research, that is, the confound of individual-level academic achievement, which switches the direction of the estimates from over- to under-representation. Conceptual issues concerning risk factors, and the relationship between cultural politics and social justice are discussed. We argue that free inquiry is a precondition for open-science practices.